한방병원에 내원한 만성 피로환자와 건강인의 심박변이도 측정을 통한 피로 진단 지표 연구 - 신선미(Seon-mi Shin); 김기태(Ki-tae Kim); 고흥(Heung Ko) (동의생리병리학회지, 2015)
This study compared the heart rate variability tests of healthy college students and chronic fatigue patients for 2 years. Study subjects were idiopathic chronic fatigue patients who carried out the HRV tests and students conducted HRV test when health screening test. Study subjects were 250 people, 104 people and men (41.6%), women were 146 patients (58.4%). In patient group, the autonomic nervous system activity was decreased, the activity of the sympathetic nerve and the parasympathetic nerve were significantly reduced compared to the control group(Patient:84.17±16.27, Control:98.33±17.28). Regardless of gender, patient group's autonomic nervous system activity was decreased, the activity of the sympathetic nerve and the parasympathetic nerve were significantly reduced, compared to the control group(Patient Female:84.17±16.27, Patient Male:84.07±14.96/Control Female:98.33±17.28, Control Male:96.45±16.92). Even though same ages, patient group's autonomic nervous activity was reduced compared to control group(Patient:89.36±12.43, Control:97.39±16.91). Fatigue patients' activity of the sympathetic nerve and the parasympathetic nerve were significantly reduced, regardless of the fact that activity of the sympathetic nerve is increased and the parasympathetic nerve is decreased in stress state like an impassioned injury(七情傷). Therefore HRV test is useful to diagnose Fatigue from this study.